Doing Gender, Doing Surveys? Women's Gatekeeping and Men's Non‐Participation in Multi‐Actor Reproductive Surveys. Issue 3 (17th June 2016) - Slauson‐Blevins, Kathleen; Johnson, Katherine M.
Abstract : Gender differences in research participation have been documented in both quantitative and qualitative studies, a pattern that is particularly pronounced in studies of reproduction. We use the National Survey of Fertility Barriers to analyze three reasons frequently used to explain men's non‐participation in reproductive research: (1) Reproduction is a sensitive subject for men, (2) reproduction is women's domain, and (3) men's unavailability due to seemingly pragmatic reasons (e.g., work schedule). Using binary logistic regression, we test these three explanations across two different models: women's gatekeeping (denying researcher access to partners) ( n = 1, 637) and men's own non‐response ( n = 1, 454). A substantial minority of women (12.8 percent), engaged in gatekeeping, but the dominant mechanism of men's non‐participation was their own non‐response once women granted researcher access to partners. Consistent with prior studies on general survey non‐response, several demographic variables were associated with men's participation. Additionally, findings suggest that the notion of reproduction as women's domain received the strongest support, though specific variables within this construct differed for models predicting women's gatekeeping versus men's non‐response of their own accord.